2016
DOI: 10.1016/j.kint.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin A receptor activation on mesangial cells initiates Alport glomerular disease

Abstract: Recent work demonstrates that Alport glomerular disease is mediated through a biomechanical strain-sensitive activation of mesangial actin dynamics. This occurs through a Rac1/CDC42 cross-talk mechanism that results in the invasion of the sub-capillary spaces by mesangial filopodia. The filopodia deposit mesangial matrix proteins in the glomerular basement membrane, including laminin 211, which activates focal adhesion kinase in podocytes culminating in the up-regulation of pro-inflammatory cytokines and metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…This study demonstrates that progressive SCBM thickening, which results in metabolic and oxidative stress in the stria vascularis of Alport mice, evolves through a mechanism that is remarkably similar to the mechanism of glomerular basement membrane disease (Dufek et al, 2016); Endothelin-1 mediated activation of ET A Rs on strial marginal cells resulting in elevated expression of ECM proteins that accumulate in the SCBMs. We show using both in vivo and in vitro systems, that ET A R blockade results in reduced ECM protein expression, normalization of SCBM thickness and reduced expression of mRNAs encoding ECM proteins that accumulate in the SCBMs.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…This study demonstrates that progressive SCBM thickening, which results in metabolic and oxidative stress in the stria vascularis of Alport mice, evolves through a mechanism that is remarkably similar to the mechanism of glomerular basement membrane disease (Dufek et al, 2016); Endothelin-1 mediated activation of ET A Rs on strial marginal cells resulting in elevated expression of ECM proteins that accumulate in the SCBMs. We show using both in vivo and in vitro systems, that ET A R blockade results in reduced ECM protein expression, normalization of SCBM thickness and reduced expression of mRNAs encoding ECM proteins that accumulate in the SCBMs.…”
Section: Discussionmentioning
confidence: 68%
“…More recently we have shown that endothelin-1 (ET-1) activates the accumulation of abnormal GBM laminins (including laminin 211) and initiates epithelial cell dysfunction in the renal glomerulus via activation of the endothelin A receptor subclass (Dufek et al, 2016). Blocking ET A Rs using sitaxentan resulted in the inhibition of ECM accumulation in the GBM and amelioration of glomerular disease initiation and progression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5, 6] The α3α4α5 type IV collagen network is more heavily cross-linked and protease-resistant than α1α1α2, and is therefore better suited for maintaining GBM integrity from increasing hydrostatic pressure to which glomeruli are exposed. [2, 79] Laminin is the most prevalent non-collagenous protein of the GBM. These cross-shaped heterotrimers consists of an α, β, and γ chain with sixteen different isoforms being identified.…”
Section: Introductionmentioning
confidence: 99%